Beat-to-beat ventricular repolarization variability evaluated during acute myocardial ischemia - Valverde, Esteban Raul (2013)
Experimental and clinical studies have shown that beat-to-beat variability of ventricular repolarization morphology, which can be measured by T-wave spectral variance (TSV) index based on the 2D-FFT, is associated with an increased risk for developing malignant ventricular arrhythmias.In the present study we tested TSV index during percutaneous coronary intervention (PCI) procedure in the 12 standard ECG leads and in the orthogonal X, Y and Z leads. In addition, we analyzed the intraindividual and interindividual variations of TSV index, in order to determine reliable limits of significant repolarization variability due to an ischemic cardiac process. The study group consisted of 62 patients, in which two ECG controls and one ECG recording during PCI procedure were obtained. Results indicate that TSV index showed significant differences during PCI procedure respect to control situation in all ECG leads(p<0.0001).The relative change between PCI procedure and control situation increased up to almost 5 times in the precordial v3 lead. Moreover, TSV index presented a high stability in each patient and a significant larger variability between patients. Finally, we conclude that TSV index offers a robust tool for evaluating beat-to-beat repolarization variability during acute myocardial ischemia.